Nutrition and diet in children with orofacial clefts in Africa: a scoping review - Kehinde Kazeem Kanmodi; Sara M. Atteya; Amira H. Elwan; Ifeoluwa Adewole; Folahanmi T. Akinsolu; Olunike R. Abodunrin; Mobolaji T. Olagunju; Jacob Njideka Nwafor; Nourhan M. Aly; Afeez Abolarinwa Salami; Moréniké Oluwátóyìn Foláyan; Maha El Tantawi (BMC, 2024)
Abstract Background and aim The burden of orofacial clefts (OFCs) has declined globally except in sub-Saharan Africa, with a great disease burden in North Africa. Children with OFCs have a high risk of malnutrition, and African countries have some of the highest malnutrition rates. This scoping review assessed the status of research on OFCs and nutrition and feeding among children living in African countries. Methods We followed the Joanna Briggs Institute guidelines for conducting scoping reviews. We searched eleven databases for articles on malnutrition and feeding among children with OFCs living in African countries. No restriction was done by type of study or publication date. Books, book chapters, and reviews were excluded. Only publications in English language were included. We extracted information about the publication year, study design, setting, location, participants' age, data collection methods, international collaboration, and funding. We classified articles into studies assessing (1) the impact of nutritional deficiencies during pregnancy on OFCs, (2) the impact of OFCs on malnutrition, (3) feeding problems in children with OFCs, and (4) the impact of nutritional status on OFCs repair outcomes. We calculated frequencies and used bar charts and a map. Results Out of 208 search results, 36 were duplicates, and 25 eventually fit the inclusion criteria, with 52% retrieved from Google Scholar. About 80% of the studies were from four countries: Nigeria, South Africa, Ghana, and Uganda; 72% were hospital-based and 52% were cross-sectional. The most frequent data collection method was clinical examination and questionnaires. Most studies focused on feeding problems in children with OFCs (44%) and the impact of OFCs on malnutrition (32%). International collaboration was observed in six studies, with one study showing South-South collaboration. Only two studies were funded. Conclusions There is a predominance of under-funded descriptive research not indexed by international databases. Minimal research has been directed to population-level OFC preventive programs in primary healthcare settings and assessing interventions supporting children with OFCs. A research agenda is needed to prioritize research needs and secure funds to support South-South collaboration to address the nutrition and feeding-related problems associated with OFCs.